Subtypes of hypertension and their association to comorbidities and ethnicity in pregnant women - Daniel Perejón López; Nancy Melissa Medrano Duarte; María Catalina Serna Arnáiz; Miriam Orós Ruiz; Júlia Siscart Viladegut; Iñaki Gascó Serna (PLoS ONE, 2025)
Objectives We analyzed the subtypes of arterial hypertension and their relationship with different comorbidities and ethnicity during pregnancy. Study design This is a retrospective observational cohort study in 17,177 pregnant women during the years 2012–2018 in the health region of Lleida. Main outcome measures We analyzed the relationship of chronic hypertension, gestational hypertension, and pre-eclampsia with different variables, including comorbidities, vascular risk factors, and ethnicity. We calculated the adjusted odds ratio (OR) and the 95% confidence interval (CI) with multivariate logistic regression models. Results The total prevalence of arterial hypertension among pregnant women was 3.10%; of these, 1.53% had chronic hypertension, 0.65% had gestational hypertension, and 0.78% had pre-eclampsia. Superimposed pre-eclampsia on chronic hypertension occurred in 25 cases (0.14%). Chronic hypertension was associated with age (OR = 1.07), overweight (OR = 4.32), obesity (OR = 2.11), diabetes mellitus (OR = 2.38), hypothyroidism (OR = 2.23), and sub-Saharan origin (OR = 3.36). Gestational hypertension was correlated with age (OR = 1.06), overweight (OR = 5.84), obesity (OR = 1.89), and Asian/Middle Eastern origin (OR = 3.71). Finally, pre-eclampsia was associated with overweight (OR = 2.37) and Sub-Saharan Africa origin (OR = 2.45). Conclusions Pregnant women with hypertension may benefit from the knowledge of the subtype and a consequent coordinated prenatal and pregnancy approach.